MENINGKATKAN HASIL BELAJAR PENJASORKES DALAM PEMBELAJARAN NARKOBA MELALUI MEDIA AUDIO VISUAL PADA SISWA KELAS X MIPA-2 SMA NEGERI 1 SIGLI - Yusnaidi Yusnaidi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
Drugs are one of the materials taught in high school (SMA) as an early effort for students to fall into the dangers of drugs, especially among teenagers at this time and in the future. However, in reality the learning process has not been carried out optimally because students are less clear in receiving material from the teacher, so students have difficulty understanding the material. This affects student learning outcomes, it is necessary to have media learning aids as a means of supporting student learning. The problem in this study is